2016
DOI: 10.1098/rsos.160057
|View full text |Cite
|
Sign up to set email alerts
|

Deceived by stripes: conspicuous patterning on vital anterior body parts can redirect predatory strikes to expendable posterior organs

Abstract: Conspicuous coloration, which presumably makes prey more visible to predators, has intrigued researchers for long. Contrastingly coloured, conspicuous striped patterns are common among lizards and other animals, but their function is not well known. We propose and test a novel hypothesis, the ‘redirection hypothesis’, wherein longitudinal striped patterns, such as those found on the anterior body parts of most lacertilians, redirect attacks away from themselves during motion towards less vulnerable posterior p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…It could be that these represent the parameters that are influenced by parallel striped conditions (Hogan, Cuthill, et al., 2016). Several of the empirical experiments on dazzle camouflage have focused on the hypothesis that bias in perceived speed could represent the primary mechanism by which this type of coloration reduces predation risk (Hall et al., 2016, Hogan et al., 2016a, Murali and Kodandaramaiah, 2016, von Helversen et al., 2013). Our results indicate that misperception in speed may not always drive the benefits of dazzle camouflage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It could be that these represent the parameters that are influenced by parallel striped conditions (Hogan, Cuthill, et al., 2016). Several of the empirical experiments on dazzle camouflage have focused on the hypothesis that bias in perceived speed could represent the primary mechanism by which this type of coloration reduces predation risk (Hall et al., 2016, Hogan et al., 2016a, Murali and Kodandaramaiah, 2016, von Helversen et al., 2013). Our results indicate that misperception in speed may not always drive the benefits of dazzle camouflage.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recent increase in research on the possible benefits of motion dazzle camouflage (Halperin et al., 2016, Hogan et al., 2016b, Hughes et al., 2015, Murali and Kodandaramaiah, 2016, Stevens et al., 2011, Stevens et al., 2008, von Helversen et al., 2013), relatively little is known about the mechanisms through which high-contrast patterns may benefit moving animals. However, it has been suggested that motion dazzle camouflage may act through the manipulation of perceived speed (Hall et al., 2016, Murali and Kodandaramaiah, 2016, Scott-Samuel et al., 2011, von Helversen et al., 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In lizards with autotomizable tails, for example, the results of Cooper & Vitt's (1991) modelling suggests that tail autotomy -and perhaps associated tail-waving behaviours -probably developed before the conspicuous colouration of these body parts in some species; this could be explored in a comparative survey across the reptiles. In lizards it has also been suggested that 'redirection' may work in combination with deflective autotomy in lizards, such that longitudinal-striped patterns on anterior body parts may redirect attacks towards less vulnerable posterior parts during motion, for example, the autotomous tail (Murali & Kodandaramaiah 2016); further study separating out functions, probably with models, could shed light on the relative role of 'redirection' in body patterns.…”
Section: Other Outstanding Questionsmentioning
confidence: 99%
“…Several lines of experimental evidence suggest that longitudinal stripes fulfill this criteria, providing effective dazzle camouflage that creates in predators an erroneous perception of the speed or trajectory of moving prey, facilitating escape (Scott‐Samuel et al. ; Murali and Kodandaramaiah ). Because longitudinal stripes are more common on diurnal non‐gekkotan squamates (Murali et al.…”
mentioning
confidence: 99%